Impact of Corona Virus pandemic on Different sectors of Nepalese Economy - Khanal, Nirdosh (Management Dynamics, 2020)
Novel coronavirus (COVID-19) causing persistent drumbeat of positive tests and reported deaths across the globe, has created widespread crisis in Nepal as well. The crisis has already led into an economic and labour market shock, impacting both on demand and supply chain. Due to the outbreak of this deadly coronavirus, Nepal has started to suffer the most abrupt and widespread cessation of economic activity. The goal of this paper is to study the emerging and rapidly growing literature on the impact of COVID-19 on various economic and social sectors and to synthetize the insights emerging from a very large number of studies. This study summarizes the literature on the socio-economic consequences of corona virus and consequent lockdown imposed by government on Nepal. This study revealed that COVID-19 has negatively impacted macro economy of country lowering national GDP, decreasing revenue collection, slowing economic growth rate, decreasing wage rate, price inflation and causing loss of employment opportunities. The study showed that almost every sector of socio-economics has been slowed down that adversely effect on country’s economy. The effect are identified on Remittance, Labour and Employment, Tourism, Education and Agriculture (Dairy, vegetables and Poultry) .The uncertain impact of the COVID-19 pandemic on Nepal’s social economy will magnify depending on how events unfold on three fronts; i) its dependence on tourism, trade, and foreign employment and the consequences that will propagate through the services and industrial landscape; ii) if or when the spread of the pandemic overwhelms a grossly inadequate health infrastructure and antivirals or vaccine become available and iii) Nepal’s heavy geo-economic reliance on India and China, and the nature of contagion in those countries.